Electrocatalytic Water Oxidation: An Overview With an Example of Translation From Lab to Market - Sen, Rakesh; Das, Supriya; Nath, Aritra; Maharana, Priyanka; Kar, Pradipta; Verpoort, Francis; Liang, Pei; Roy, Soumyajit (Frontiers in Chemistry, 2022)
Water oxidation has become very popular due to its prime role in water splitting and metal–air batteries. Thus, the development of efficient, abundant, and economical catalysts, as well as electrode design, is very demanding today. In this review, we have discussed the principles of electrocatalytic water oxidation reaction (WOR), the electrocatalyst and electrode design strategies for the most efficient results, and recent advancement in the oxygen evolution reaction (OER) catalyst design. Finally, we have discussed the use of OER in the Oxygen Maker (OM) design with the example of OM REDOX by Solaire Initiative Private Ltd. The review clearly summarizes the future directions and applications for sustainable energy utilization with the help of water splitting and the way forward to develop better cell designs with electrodes and catalysts for practical applications. We hope this review will offer a basic understanding of the OER process and WOR in general along with the standard parameters to evaluate the performance and encourage more WOR-based profound innovations to make their way from the lab to the market following the example of OM REDOX.